Formation of Quasi-2D [Mon+1Cn] Layered Structures via Carburizing Metal Films toward Surface Functional Group-Free Molybdenum Carbide MXene Thin Films - Junhyeok No; Taemin Ahn; Tae-Hwan Kim; Hee Cheul Choi (Journal of the American Chemical Society, 2026)
Abstract MXenes have a characteristic quasi-two-dimensional structure composed of covalently bonded transition metal (M) and carbon or nitrogen (X) sublayers, [Mn+1Xn], stacked with an interlayer spacing. Conventional MAX-etched MXenes inevitably have inhomogeneous surface functional groups (Tx), while chemical vapor deposition (CVD) has so far yielded only ultrathin α-Mo2C bulk crystals, failing to form a layered structure. Here, we report a CVD approach that enables the formation of layered [Mon+1Cn] structures through controlled carburization of predeposited Mo films without Tx sources. The resulting films are composed of multiple MXene phases, including Mo2C, Mo3C2, and Mo4C3 layered motifs. Regulated carbon diffusion results in discrete [Mon+1Cn] slabs with a well-defined interlayer spacing. In addition, a signature Tx-free, Mo-exposed surface exhibits enhanced nitrogen reduction reaction (NRR) activity compared with a CVD-grown α-Mo2C film, achieving an NH3 yield of 6.52 μg h–1 cm–2. Given the broad applicability to other MXenes, we anticipate that this work will stimulate further fundamental research and application on MXenes.